COLLEMBOLA DIVERSITY IN THE SOIL OF THE THREE TYPES OF LAND USED ON BUNGO DISTRICT JAMBI PROVINCE, INDONESIA - Febriyansyah (International Journal of Research -GRANTHAALAYAH, 2017)
The research regarding Collembola on Bungo District was conducted from February to July 2014. The purpose of this study was to know Collembola Diversity in the soil of the three types of land used (secondary forest, rubber plantation and palm plantation). This study used a purposive sampling method with soil drill having 4 cm diameter. The highest diversity on three types of land use is on rubber plantation and the lowest is on secondary forest. Family Entomobryidae (Ascocyrtus sp.) has the highest number of species as well as the highest percentage of all species.